In Situ Peroxidase Labeling Followed by Mass-Spectrometry Reveals TIA1 Interactome - Olga Gourdomichali; Katerina Zonke; Fedon-Giasin Kattan; Manousos Makridakis; Georgia Kontostathi; Antonia Vlahou; Epaminondas Doxakis (Biology, 2022)
TIA1 is a broadly expressed DNA/RNA binding protein that regulates multiple aspects of RNA metabolism. It is best known for its role in stress granule assembly during the cellular stress response. Three RNA recognition motifs mediate TIA1 functions along with a prion-like domain that supports multivalent protein-protein interactions that are yet poorly characterized. Here, by fusing the enhanced ascorbate peroxidase 2 (APEX2) biotin-labeling enzyme to TIA1 combined with mass spectrometry, the proteins in the immediate vicinity of TIA1 were defined in situ. Eighty-six and 203 protein partners, mostly associated with ribonucleoprotein complexes, were identified in unstressed control and acute stress conditions, respectively. Remarkably, the repertoire of TIA1 protein partners was highly dissimilar between the two cellular states. Under unstressed control conditions, the biological processes associated with the TIA1 interactome were enriched for cytosolic ontologies related to mRNA metabolism, such as translation initiation, nucleocytoplasmic transport, and RNA catabolism, while the protein identities were primarily represented by RNA binding proteins, ribosomal subunits, and eicosanoid regulators. Under acute stress, TIA1-labeled partners displayed a broader subcellular distribution that included the chromosomes and mitochondria. The enriched biological processes included splicing, translation, and protein synthesis regulation, while the molecular function of the proteins was enriched for RNA binding activity, ribosomal subunits, DNA double-strand break repair, and amide metabolism. Altogether, these data highlight the TIA1 spatial environment with its different partners in diverse cellular states and pave the way to dissect TIA1 role in these processes.